KAJIAN PROSES DEGRADADI BAHAN ORGANIK LIMBAH CAIR SELAMA AKLIMATISASI PADA KONDISI ANAEROBIK DENGAN KONSENTRASI GARAM TINGGI - Mega Ayu Yusuf (Universitas Musamus, Merauke, Papua, 2012)
Waste with high level of salinity is usually difficult for microorganism to degrade because the high level of salinity concentration in the environment can hamper microorganism to reduce organic materials. This research was aimed at studying degradation process of organic materials in anaerobic condition with high level of salinity concentration. The main research was conducted with three operation conditions with inoculum as much as 15% out of total sample volume in which a number treatments in terms of adding salt fiom 0 mg/kg, 32 mg/kg and 52 mg/kg. This research was used some synthetic liquid waste (molases) with inoculum came fiom salt made location. The initial COD content in molases which has been made into liquid is averagely out of two test was 400000 mg/l. The COD content required for this research was 4000 mg/l.